Global rice price declines and expected effects on monsoon paddy farming: Insights from key informants - Minten, Bart; Aung, Zin Wai; Htar, May Thet; Masias, Ian (International Food Policy Research Institute, 2025)
This brief draws on interviews with 51 agro-input retailers across 10 states and regions to assess how falling international rice prices may affect monsoon paddy cultivation in their communities.